Detection and identification of a 16SrIII-J phytoplasma affecting cassava (Manihot esculenta Crantz) in Argentina - Fernandez, Franco Daniel; Uset, Ovidio Antonio; Baumgratz, Gustavo; Conci, Luis Rogelio (Springer; Australasian Plant Pathology Society, 2018)
Cassava plants displaying symptoms of dwarfing, witches’ broom, and chlorosis, were detected in production fields located in Misiones province Argentina. The RFLP profiles and phylogenetic analyses based on 16S rRNA and ribosomal protein (rplV-rpsC) gene sequences, allowed assignment of the phytoplasma detected in cassava to the 16SrIII-J subgroup. This is the first report of a phytoplasma affecting cassava in Argentina.